Double blind, controlled trial of 4-aminosalicylic acid and prednisolone enemas in distal ulcerative colitis. Issue 7 (July 1992) - O'Donnell, L J; Arvind, A S; Hoang, P; Cameron, D; Talbot, I C; Jewell, D P; Lennard-Jones, J E; Farthing, M J
Abstract : Corticosteroid or 5-aminosalicylic acid enemas are the treatment of choice for distal ulcerative colitis but up to one third of patients may be unresponsive. As an alternative therapy might be advantageous, the efficacy of six weeks' treatment with 2 g 4-aminosalicylic acid (4-ASA) (n = 24) and 20 mg prednisolone enemas (n = 21) were compared in a double blind, randomised trial in patients with acute distal (less than 30 cm from the anus) ulcerative colitis. Baseline demography and clinical severity were similar in both groups. Five of 24 patients receiving 4-ASA and 4 of 21 receiving prednisolone did not complete the trial because of deteriorating symptoms, failure to improve, or side effects. At the time of leaving the trial, 24 hour stool frequency, the presence of blood in the stools, and histological and sigmoidoscopic appearances were similar in both groups. Symptomatic improvement occurred in 17 of 24 patients receiving 4-ASA compared with 11 of 21 receiving prednisolone (chi 2 = 1.62, NS). Complete symptomatic improvement occurred in 9 of 24 patients receiving 4-ASA compared with 5 of 21 receiving prednisolone (chi 2 = 0.98, NS). Histological improvement was seen in 9 of 24 patients on 4-ASA compared with 7 of 21 on prednisolone (chi 2 = 0.08, NS). One patient receiving 4-ASA was considered to have an idiosyncratic reaction to the drug but other side effects were not considered to be drug related. Thus, 4-ASA, previously used in the treatment of tuberculosis (para-aminosalicyclic acid), is as good as prednisolone in the treatment of distal ulcerative colitis and should be considered in patients unresponsive to steroids or in whom steroid treatment is undesirable.